Importance of breast self-examination in the timely detection of cancer - Luannys de la Caridad Garau Rivero; Yaima Labrada García (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2021)
Breast cancer continues to be a scourge for women's health. Its early detection is a guarantee to achieve its eradication and guarantee a better quality of life to those who suffer from it. Performing a breast self-exam plays an important role in this regard, however it is not a common practice among women. Reflecting on this is the aim of this work.